Signs, Symbols, and Identity: A Semiotic Reinterpretation of Javanese Womanhood in “Losmen Bu Broto” - Kholiq, Muh.; Ningsih, Sri; Dinda Amelia, Rizki (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2025)
While traditional depictions of Javanese women in media have often reinforced stereotypes of submissiveness, gentleness, and familial devotion, such portrayals are increasingly being redefined in contemporary Indonesian cinema. This study investigates how Javanese women are represented in the film Losmen Bu Broto, a modern adaptation of the classic TVRI series, through a qualitative descriptive method using John Fiske’s semiotic framework of television codes. The analysis examines three key levels of meaning: reality, representation, and ideology, focusing on narrative structure, character behavior, costuming, and cinematographic techniques. The findings reveal a spectrum of female identities within the film, ranging from the traditional and compliant Pur to the modern, expressive Sri, and the authoritative, business-minded Madam Broto. Although the film retains strong cultural symbols such as the kebaya and konde, these are interwoven with contemporary expressions of autonomy, emotional complexity, and leadership. These layered representations challenge the singular image of the Javanese woman as passive and instead present her as multidimensional and evolving. The study contributes to the growing discourse on gender representation in Southeast Asian media, offering a nuanced understanding of how cultural identities are both preserved and contested through film. In a broader context, this research highlights the role of visual media in shaping public consciousness and advancing more inclusive and dynamic narratives of womanhood within Indonesian society.